The Use of the Quizizz Application as Instructional Media and Its Effect on Senior High School Students’ Learning Motivation - Tria Ratna Dewi; Marlena Marlena (Indonesian Journal of Innovative Teaching and Learning, 2026)
Background: The rapid development of educational technology has encouraged the integration of digital learning media to enhance student engagement and motivation, particularly in secondary education contexts. Objective:  This study aims to examine the use of the Quizizz application as a learning medium and its effect on senior high school students’ learning motivation at SMA Negeri Bareng. Method:  This study employed a qualitative descriptive approach. Data were collected through classroom observations, semi-structured interviews with teachers and students, and documentation. Data analysis was conducted using data reduction, data display, and verification techniques. Findings:  The findings reveal that Quizizz use positively influences students’ learning motivation by creating an interactive, enjoyable, and competitive learning environment that promotes active participation, focus, and enthusiasm during learning activities. Some challenges related to time management and competition pressure were also identified. Conclusion:  The study concludes that Quizizz is a feasible and effective technology-based learning medium for enhancing learning motivation among senior high school students. Contribution:  This research contributes to the literature on gamified learning media by providing empirical evidence of Quizizz’s effectiveness in motivating senior high school students. It offers practical guidance for teachers and schools in implementing interactive digital learning tools.